Shifts in Structure and Assembly Processes of Root Endophytic Community Caused by Climate Warming and Precipitation Increase in Alpine Grassland - Xiaoting Wei; Bing Han; Jinxin Zhang; Xinqing Shao (Microorganisms)
Climate change poses great challenges to the survival of plants. Plant endophytes play important roles in improving plant adaptability. However, our knowledge of the effects of climate change on endophytic community structures is limited. Relying on a field experimental platform simulating climate warming, precipitation increases, and their combination in an alpine grassland, the root endophytic bacterial community structures and assembly processes of three coexisting plant species (Elymus nutans, Kobresia humilis, and Melissilus ruthenicus) were measured. The results indicated that Proteobacteria was the dominant phylum, with a relative abundance ranging from 50% to 80%, followed by Actinobacteria and Bacteroidetes. Bacterial diversity decreased significantly under the combined treatment for all three plant species, with the largest reduction observed in E. nutans. The climate manipulation treatments had a minimal effect on the endophytic bacterial community structures. The relative abundance of Burkholderiaceae increased significantly under the combined treatment for the three plant species. Moreover, the endophytic community assembly processes changed from stochastic dominated under control plots to deterministic dominated under the combined plots for E. nutans, while this shift was reversed for M. ruthenicus. The root endophytic bacterial community was affected by the soil’s available nitrogen and stoichiometric ratio. These results revealed that the sensitivity of endophyte community structures to climate change varies with host plant species, which has implications for plant fitness differences.